The Impact of the Covid-19 Pandemic on Halal-Certified Culinary Micro, Small, and Medium Enterprises (MSMEs) in Welcoming Indonesian Halal Tourism in 2023 - Indah Kurniawati; Beni Suhendra Winarso; Siska Lidya Revianti (Proceedings of Femfest International Conference on Economics, Management, and Business, 2023)
The Covid 19 pandemic, which became a worldwide epidemic in early 2020, has devastated the world economy, including Indonesia. The Covid-19 pandemic affected all parts of human lives. In the business sector, not only Micro, Small, and Medium-sized Enterprises (MSMEs) but also large companies in many countries affected by the Covid-19 pandemic. This study analyzed and tested the significant differences in productivity, turnover, and utilization of digital marketing in halal-certified culinary MSMEs. The government has given great attention, followed by supporting policies encouraging MSMEs to adapt to the digital era immediately. The government launched much digital marketing training and the Sehati program (Sertifikasi Halal Gratis or Free Halal Certification) in welcoming Indonesia as Halal tourism in 2023. This study used primary data from a questionnaire given to MSMEs in the culinary field that has been certified halal. The test used the Kolmogorov Smirnov one sample normality test, and the different tests used the Wilcoxon Signed Rank Test. The results showed that productivity, business turnover, and the use of digital marketing for MSMEs in the culinary field were significantly different before and during the Covid-19 pandemic. This result showed that the Covid-19 pandemic has significantly impacted the culinary industry even though it has been certified halal due to implementing healthy protocols such as keeping a distance, avoiding crowds, and maintaining cleanliness and hygiene.